High-field EPR investigations of Mn(III)Mn(IV) and Mn(II)Mn(III) states of dimanganese catalase and related model systems - Teutloff, Christian (Magnetic resonance in chemistry : MRC, 2005)
Copyright 2005 John Wiley & Sons, Ltd